2015
DOI: 10.1016/j.abb.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to catalysis of ornithine binding residues in ornithine N5-monooxygenase

Abstract: The SidA ornithine N5-monooxygenase from Aspergillus fumigatus is a flavin monooxygenase that catalyzes the NADPH-dependent hydroxylation of ornithine. Herein we report a mutagenesis study targeting four residues that contact ornithine in crystal structures of SidA: Lys107, Asn293, Asn323, and Ser469. Mutation of Lys107 to Ala abolishes activity as measured in steady-state oxygen consumption and ornithine hydroxylation assays, indicating that the ionic interaction of Lys107 with the carboxylate of ornithine is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
16
1
Order By: Relevance
“…Four residues involved in ornithine binding were individually changed to Ala (Robinson et al 2015 ). The Lys107Ala variant lost its hydroxylation activity, indicating that the ionic interaction between Lys107 and the substrate carboxylate is essential for catalysis.…”
Section: Catalytic Mechanism Of Flavin-dependent Nmosmentioning
confidence: 99%
“…Four residues involved in ornithine binding were individually changed to Ala (Robinson et al 2015 ). The Lys107Ala variant lost its hydroxylation activity, indicating that the ionic interaction between Lys107 and the substrate carboxylate is essential for catalysis.…”
Section: Catalytic Mechanism Of Flavin-dependent Nmosmentioning
confidence: 99%
“…SidA is an enzyme specific for hydroxylation of ornithine, a precursor molecule of ferricrome siderophores biosynthesis (Chocklett and Sobrado 2010 ). The three-dimensional structure of SidA in A. fumigatus demonstrates the presence of amino acid residues essential for both NAPDH association and ornithine binding and hydroxylation (Robinson et al 2015 ; Robinson et al 2014 ). In this sense, SidA structure from P. brasiliensis was studied since the capacity of ornithine hydroxylation and use of NADPH as cofactor are specific to this enzyme (Chocklett and Sobrado 2010 ), which are influenced by the amino acids present in its structure (Robinson et al 2014 ; Robinson et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional structure of SidA in A. fumigatus demonstrates the presence of amino acid residues essential for both NAPDH association and ornithine binding and hydroxylation (Robinson et al 2015 ; Robinson et al 2014 ). In this sense, SidA structure from P. brasiliensis was studied since the capacity of ornithine hydroxylation and use of NADPH as cofactor are specific to this enzyme (Chocklett and Sobrado 2010 ), which are influenced by the amino acids present in its structure (Robinson et al 2014 ; Robinson et al 2015 ). The characterization of the three-dimensional SidA structure of P. brasiliensis was performed by molecular modeling based on A. fumigatus crystal, which is most similar structure available (Sanchez et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, steady-state kinetics have shown that substrate binding (Km(L-Orn)) was increased ~ 15-fold with no observed effect on NADPH binding. Thus, N323 was proposed to hydrogen bond with the nicotinamide ribose of 17 NADPH as well as contribute to L-Orn binding to balance flavin reduction and substrate binding [14]. In Sida, the interaction of N323 with NADPH was proposed to regulate the position of NADP + , which is believe to require significant movement [22].…”
Section: Indeed P238 Orientation Shows Clashes With the Nadp(h) Molementioning
confidence: 99%
“…NbtG is a member of the class B flavin monooxygenases, and is grouped under the subfamily of N-hydroxylating monooxygenases (NMOs) [12]. The best characterized NMOs are the L-ornithine (L-Orn) monooxygenases from Aspergillus fumigatus (SidA) and Pseudomonas aeruginosa (PvdA) [13][14][15][16][17][18]. SidA displays an ~ 20-fold preference for NADPH over NADH, while PvdA is only able to react with NADPH [13,19,20].…”
Section: Introductionmentioning
confidence: 99%